Motivational Self System among Secondary Schools Students in Urban and Rural Place (RETAIN, 2020)
The current study investigated the L2 motivational self-system among students in secondary schools from urban and rural place. It was aimed to see whether any different L2 motivational self-system among students in two different learning places also in two different levels of study. The questionnaires were distributed to secondary schools’ students in Surabaya and Lamongan and the result showed that ideal L2 self aspect got the highest score in descriptive statistic from the two different learning places. Later, the independent t-test indicated that students in urban and rural place experienced different learning environment that lead them to have different support in learning English. The other significant results were also found in the other related aspects except language anxiety, peer influence and family influence. Furthermore, junior high school and senior high school students were found statistically different only in aspect of L2 learning experience in school.